Agile learning in marketing: Scrum in higher education - Aragonés-Jericó, Cristina; Canales-Ronda, Pedro (Journal of Management and Business Education, 2022)
The main objective of this article is to show the results of a teaching innovation project that proposes the use of agile methodologies, typical of the business world, to adapt them to teaching. To this end, the agile technique Scrum is applied, a practical and experiential method in which learning by doing is used. Scrum facilitates the development of important skills for the students' future employment (working under pressure, adapting to new situations, teamwork, communication and conflict management). The specific objectives of the project are: 1. To design practical classes based on Scrum. 2. To use digital technologies and resources efficiently. 3. To bring the university and business worlds closer together. 4. To measure the perception of university students after the application of the teaching innovation project. To analyze descriptive results, a survey was carried out among the students who participated in the project, reaching a sample of 425 students (Faculty of Economics, University of Valencia). Most of them have had previous experience with learning-by-doing methodologies and consider them much more useful than the traditional methodology. The aspects they value most highly in the agile methodology are team performance, interactivity and commitment. In addition, the students involved mainly value them as interesting, entertaining, useful and dynamic.